Estimating the Services Sector Impact on Economic Growth of Bangladesh: An Econometric Investigation - Yousuf, Md.; Ahmed, Raju; Lubna, Nasrin Akther; Sumon, Shah Md. (Asian Journal of Economic Modelling, 2019)
This study attempts to examine the contribution of the service related sector in the economic growth of Bangladesh during the period of 1973-2017. We used the Gross domestic product (GDP) as a measure of economic growth for Bangladesh. Sub-sectors of service-related sector have been used as explanatory variables along with some control variables. In this study, we apply various econometric tools like as Unit Root test, Granger causality test, ARDL Bound test, Error correction model and Co-integration test to investigate the causal relationship and the intensity of the relationship between the service related sector and gross domestic product or economic growth. Granger causality test shows the presence of uni-directional granger causality from the service related sector to gross domestic product. The error correction term implies that the short-run disequilibrium is adjusted with the long-run at the speed of 17 percent. Moreover, ARDL bound approach indicates the service related sector and gross domestic product growth are correlated both in short-run and long-run. The result shows that 1% expansion in service-related sector will result in an increase of 0.64% gross domestic product or economic growth in short-run and 0.75% of GDP in the long-run.